Ketamine-Medetomidine-Midazolam and Ketamine- Dexmedetomidine-Midazolam anesthesia in gerbils: a clinical comparison of subcutaneous and intraperitoneal administration - Nimet Kılıç; Nuh Kılıç; Burak Baydoğan (Revista Científica de la Facultad de Ciencias Veterinarias, 2026)
This study investigated the anesthetic performance and cardiopulmonary effects of ketamine-medetomidine-midazolam and ketamine-dexmedetomidine-midazolam combinations administered by subcutaneous or intraperitoneal routes in gerbils. Thirty-two clinically healthy male gerbils were allocated to four experimental groups according to the anesthetic protocol and route of administration. All protocols produced satisfactory sedation and surgical anesthesia without mortality. Induction was achieved in all animals within a relatively short period, and dexmedetomidine- containing combinations tended to induce anesthesia more rapidly than medetomidine-based protocols. The duration of surgical anesthesia was significantly longer in animals receiving dexmedetomidine, indicating a more prolonged anesthetic effect. Throughout the observation period, significant alterations were recorded in heart rate, respiratory rate, body temperature, and peripheral oxygen saturation. Cardiopulmonary depression was observed in all groups but was more evident in animals receiving dexmedetomidine. Intraperitoneal administration generally resulted in a faster onset of anesthesia and more pronounced physiological effects compared with subcutaneous administration. Although reductions in cardiovascular and respiratory parameters were detected, no life-threatening complications occurred and although oxygen saturation values remained compatible with spontaneous recovery, transient decreases observed in dexmedetomidine-treated animals suggest that oxygen supplementation should be considered during prolonged anesthetic procedures. Recovery tended to occur earlier in medetomidine- treated gerbils, whereas dexmedetomidine produced a longer- lasting anesthetic state. The findings indicate that both anesthetic combinations can be safely used in gerbils under appropriate monitoring conditions. Dexmedetomidine provided a longer and deeper anesthetic effect, while subcutaneous administration offered a more gradual anesthetic profile with less pronounced physiological depression.